2000
DOI: 10.1046/j.1440-1681.2000.03380.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes In Absorptive Function Of Rat Intestine Injured By Methotrexate

Abstract: 1. Methotrexate (MTX), an anticancer drug, has been shown to induce acute injury in the small intestine. The present study was designed to investigate the in vivo absorptive function of the small intestine injured by MTX using an amino-beta-lactam antibiotic cephalexin (CEX). Time-dependent changes in diamine oxidase (DAO) and alkaline phosphatase (ALP) activity in the small intestine and histopathological findings were also measured in rats treated with MTX (20 mg/kg). 2. Most severe mucosal damage was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…24 MTX has been shown to induce shortening or fusion of villi, and both atrophy and desquamation of the surface epithelium in various studies. [26][27][28] In the present study, the tissue sections of the rats showed normal intestinal structures in the salinetreated group. The barrier of intestinal mucosa integrity was changed and villus atrophy was remarkable in rats treated with MTX.…”
Section: Discussionsupporting
confidence: 57%
“…24 MTX has been shown to induce shortening or fusion of villi, and both atrophy and desquamation of the surface epithelium in various studies. [26][27][28] In the present study, the tissue sections of the rats showed normal intestinal structures in the salinetreated group. The barrier of intestinal mucosa integrity was changed and villus atrophy was remarkable in rats treated with MTX.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, the general characteristics (villus atrophy, crypt loss, goblet cell depletion) of MTX-induced small intestinal mucositis were the same as described in previous studies [4,19,20]. Proliferation of small intestinal epithelial cells occurs in the crypts.…”
Section: Discussionmentioning
confidence: 62%
“…Methotrexate (MTX) is an anticancer drug that has been shown to be highly effective against various malignancies [1]. The antimitotic effect of MTX is known to give rise to the malabsorption syndrome [2][3][4] that decreases the surface area for absorption caused by histological alterations such as shortened microvilli, resulting in less absorption of nutrients [5]. In addition, MTX depresses absorption of certain drugs from the small intestine [5], metabolic activity and active transport capacity of the intestinal mucosa [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mucositis is characterized by major morphologic changes of the intestinal epithelium, such as epithelial flattening, villus atrophy, and specific down-regulation of the enterocytespecific gene expression that is crucial for degradation and absorption of nutrients (3)(4)(5). It is unknown how this condition effects digestion and absorption of enteral nutrition.…”
mentioning
confidence: 99%